1995
DOI: 10.1007/bf00806825
|View full text |Cite
|
Sign up to set email alerts
|

Anodically generated manganese(III) acetate for the oxidation of ? ? amino acids in aqueous acetic acid: A kinetic study

Abstract: Manganese(III) acetate was prepared by the oxidation of manganese(II) acetate in aqueous acetic acid by electrolytic method. The anodically generated Mn(III) species was characterised by spectroscopic and redox potential studies. Conditions for the study of kinetics of Oxidation ofα-amino acids by Mn(III) in aqueous acetic acid was investigated. Plots of log[Mn(III)] versus time for the first order process, or Mn(III) versus time for zero order process were nonlinear. The rate constants computed from [Mn(III)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Several studies have been reported on the kinetics of oxidation of AAs by various oxidants in different media [3,4]. Most of the previous kinetic investigations provide information about reaction mechanism, thermodynamic parameters, activation parameters [5], and oxidative reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on the kinetics of oxidation of AAs by various oxidants in different media [3,4]. Most of the previous kinetic investigations provide information about reaction mechanism, thermodynamic parameters, activation parameters [5], and oxidative reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] There are several reports of oxidation of various substrates by Mn(III) in acid solutions containing such salts as perchlorate, sulfate, acetate, and pyrophosphate. [7][8][9][10][11][12][13] A study of the kinetics and mechanism of oxidation of DL-Ala by Mn(III) in aqueous acetic acid solutions is reported here.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] There are several reports of oxidation of various substrates by Mn(III) in perchlorate, sulfate, acetate and pyrophosphate media. [7][8][9][10][11][12][13][14] Non-sulfur containing amino acids and amines usually undergo oxidation via deamination to the corresponding aldehydes. Since sulfur is a preferred site of oxidation, amino acids such as Met undergo oxidation to the corresponding sulfoxide or sulfone.…”
Section: Introductionmentioning
confidence: 99%